MRP8 promotes Th17 differentiation via upregulation of IL-6 production by fibroblast-like synoviocytes in rheumatoid arthritis - Lee, Dong-Gun (Nature Publishing Group, 2013)
Myeloid-related protein (MRP)8/MRP14 is an endogenous Toll-like receptor 4 (TLR4) ligand and is abundant in synovial fluid (SF) of rheumatoid arthritis (RA) patients. Belonging to damage-associated molecular patterns, it amplifies proinflammatory mediators and facilitates a wide range of inflammatory and autoimmune diseases. Interleukin (IL)-17-producing T-helper (Th)17 cells have a crucial role in RA pathogenesis, and IL-6 is the key factor promoting Th17 differentiation. We investigated whether the level of MRP8/MRP14 is positively associated with IL-6 and IL-17 levels in RA SF and found that MRP8/MRP14 level had a significant correlation with IL-6 and IL-17 levels in RA SF. We also observed that MRP8-induced IL-17 production by peripheral blood mononuclear cells but MRP14 did not. Upon stimulation with MRP8, IL-6 production was enhanced by RA fibroblast-like synoviocytes (FLS) and was further elevated by coculturing RA FLS with activated CD4(+) T cells. Moreover, we demonstrated that MRP8-activated IL-6 production by RA FLS promoted differentiation of Th17 cells using the coculture system consisting of CD4(+) T cells and RA FLS. In addition, IL-6 blockade attenuated Th17 polarization of CD4(+) T cells in the cocultures. Inhibitor studies revealed that MRP8 increased IL-6 production in RA FLS via TLR4/phosphoinositide 3-kinase/nuclear factor-κB and mitogen-activated protein kinase signaling pathways. Our results show that MRP8 has a crucial role in stimulating IL-6 expression by RA FLS, and subsequently promotes Th17 differentiation in RA, suggesting that neutralizing MRP8 level in RA synovium may be an effective therapeutic strategy in RA treatment.